Istikhdām ṭarīqat al-qawāʿid wa-al-tarjamah fī taʿlīm Kitāb Sullam al-Munājāh wa-atharuhā bi-qudrat al-talāmīdh ʿalā qirāʾatih - Siti Nurazizah, Fida; Fajar, Ahmad; Luthfi, Taufik (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
The use of the qowa’id wa tarjamah method in learning the Sulam al-Munajat book and its effect on students’ ability to read it. The purpose of this study was to determine the use of the qowa’id wa tarjamah method in learning the Pola utturosh Kitab Sulam al-Munajat and the impact of the use of the qowa’id wa tarjamah method on reading skills. Arabic learning to speakers of other languages â€‹â€‹today comes from the basic teachings of foreign languages â€‹â€‹and teaching methods. One of the well-known methods in the field of foreign language teaching is the qowa’id wa tarjamah method. The qowa’id wa tarjamah method is a method consisting of grammar and translation methods. the key in his teaching is to explain the grammar and teach it to other language skills especially in reading and translating skills. Then, the teaching of grammar became the end of his teaching. Therefore there is a correlation between the qowa’id wa tarjamah method and reading skills. This research is a quantitative research that deals with two variables. The type of research is case research. The researcher used books and field data sources to write this research. The researcher used the data collection method by distributing questionnaires, testing, observation and documentation. The data analysis method was carried out using Microsoft Excel to collect data first and then using the SPSS application (Statistical Package of Social Science) for statistical computing activities. The fact that the use of the qowa’id wa tarjamah method in learning the book of Sulam al-Munajat shows a very good publication because the results of data analysis show an average limit of 88. 42% or 88. 42%. The ability to read is implemented with good publications because the results of data analysis show an average limit of 83. 96% or 84%, and the fact that the use of the qowa’id wa tarjamah method has an impact on students’ reading abilities of an R coefficient of 0. 573. variable X has an effect on variable Y by 0. 57%. while the rest is influenced by other factors.